Differences in cancer patients' and clinicians' preferences for disclosure of uncertain genomic tumor testing results. Issue 1 (January 2021) - Fenton, Anny T.; Anderson, Eric C.; Scharnetzki, Elizabeth; Reed, Kate; Edelman, Emily; Antov, Andrey; Rueter, Jens; Han, Paul K.J.; ,
Highlights: A greater share of cancer patients than clinicians prefer disclosure of GTT results. Patient preferences are less sensitive to uncertainty regarding actionability. Uncertainty sensitivity in disclosure preferences is associated with GTT attitudes. Among patients, uncertainty sensitivity is associated with uncertainty tolerance. Patients' and clinicians' differing disclosure preferences are important to address. Abstract: Objective: To compare clinicians' and patients' preferences for disclosure of genomic tumor testing (GTT) results; to determine the sensitivity of these disclosure preferences to uncertainty about the actionability of results; and to explore factors associated with disclosure preferences. Methods: Community-based oncology clinicians (n = 94) and patients (n = 1121) were surveyed about their preferences for disclosing GTT results with varying levels of uncertainty (Tiers 1, 2, 3). Descriptive and multivariable regression analyses were used to compare clinicians' and patients' disclosure preferences and their sensitivity to uncertainty, and to explore associations between disclosure preferences and sociodemographic, clinical, and psychological factors. Results: Relatively more patients than clinicians preferred disclosure, and their preferences were less sensitive to the uncertainty of GTT results. For patients and clinicians, lower uncertainty sensitivity was associated with positive GTT attitudes; for patients it was also associated with greater uncertainty tolerance and knowledge of uncertainty in GTT. Conclusion: Relatively more cancer patients than clinicians prefer disclosure of GTT results, and their preferences are less sensitive to result uncertainty. Uncertainty sensitivity in disclosure preferences is associated with GTT-related attitudes and uncertainty tolerance. Practice implications: Differences in cancer patients' and clinicians' preferences for disclosure of uncertain GTT results warrant greater attention in cancer care.